2007
DOI: 10.1016/j.foodcont.2006.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lactic acid and lauricidin on the survival of Listeria monocytogenes, Salmonella enteritidis and Escherichia coli O157:H7 in chicken breast stored at 4 °C

Abstract: Lauricidin and lactic acid were evaluated for their eVects on growth and survival of Listeria monocytogenes (L55), Salmonella enteritidis (S552) and Escherichia coli O157:H7 (E19) inoculated onto raw chicken breast. Fresh, raw chicken breasts were purchased immediately after slaughter and transported on ice to the laboratory within 20 min. Each chicken breast was decontaminated by brieXy dipping in 70% ethanol and passed through a Xame of a Bunsen burner and then allowed to cool. The decontaminated Chicken bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 33 publications
(44 reference statements)
3
55
0
3
Order By: Relevance
“…The recognition of coconut oil antimicrobial activities was also reported by Hierholzer and Kabara [42] which focused on virucidal effects of monolaurin RNA and DNA viruses. Recently, experimental outcomes from many studies discovered that monolaurin had not only antimicrobial activity against various gram-positive and gram-negative bacterial cells [1,3,43] but also antifungal and antiviral properties [44,45,46,47,48]. Manohar et al [49] showed that coconut oils, when used as food flavouring agents, exhibited a wide range of antimicrobial activities.…”
Section: Antimicrobial Activities Of Virgin Coconut Oilmentioning
confidence: 99%
“…The recognition of coconut oil antimicrobial activities was also reported by Hierholzer and Kabara [42] which focused on virucidal effects of monolaurin RNA and DNA viruses. Recently, experimental outcomes from many studies discovered that monolaurin had not only antimicrobial activity against various gram-positive and gram-negative bacterial cells [1,3,43] but also antifungal and antiviral properties [44,45,46,47,48]. Manohar et al [49] showed that coconut oils, when used as food flavouring agents, exhibited a wide range of antimicrobial activities.…”
Section: Antimicrobial Activities Of Virgin Coconut Oilmentioning
confidence: 99%
“…The major bacteria that are present in poultry products are E. coli, Salmonella spp. Listeria monocytogenes, and Campylobacter jejuni (Anang et al, 2007 andHong et al, 2008).…”
Section: Issn: 2319-7706 Volume 7 Number 02 (2018)mentioning
confidence: 99%
“…W piśmiennictwie jest niewiele danych dotyczą-cych wpływu kwasu mlekowego na wzrost pałeczek Salmonella na tuszkach kurcząt (3,8,9). Uzyskane wyniki badań własnych, potwierdzają rezultaty badań innych autorów, którzy stosując spryskiwanie 2% kwasem mlekowym przez 17 do 180 sekund uzyskali redukcję zanieczyszczenia od 0,73 do 2,2 log (9, 19-21).…”
Section: Wyniki I Omówienieunclassified